2017
DOI: 10.4300/jgme-d-16-00847.1
|View full text |Cite
|
Sign up to set email alerts
|

Attending Physician Remote Access of the Electronic Health Record and Implications for Resident Supervision: A Mixed Methods Study

Abstract: Background Advances in information technology have increased remote access to the electronic health record (EHR). Concurrently, standards defining appropriate resident supervision have evolved. How often and under what circumstances inpatient attending physicians remotely access the EHR for resident supervision is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For example, the following three suggestions are ways designers could leverage what was learned from this study and implement it: (1) auto-populating patient information into a “snap-shot” view that presents as the landing page for the selected patient and matches format, layout, and content found on the “brains” that is printable to at most a single page per patient; (2) allowing space for informal, short-term, personal notes or adding annotation features, and (3) providing a program or application that allow nurses to easily design an electronic “brain” that auto-populates the selected data. Similarly, the vast majority of attending physician supervisors have been found to remotely monitor and act upon information to improve care which would not otherwise have been detected with the opportunities provided by remote real-time access via the EHR (Martin, Tulla, Meltzer, Arora, & Farnan, 2017). A remotely monitored supervisory function could similarly be performed with nursing administrators in that nurse managers could review the data from “brains” of junior nursing personnel to identify training.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the following three suggestions are ways designers could leverage what was learned from this study and implement it: (1) auto-populating patient information into a “snap-shot” view that presents as the landing page for the selected patient and matches format, layout, and content found on the “brains” that is printable to at most a single page per patient; (2) allowing space for informal, short-term, personal notes or adding annotation features, and (3) providing a program or application that allow nurses to easily design an electronic “brain” that auto-populates the selected data. Similarly, the vast majority of attending physician supervisors have been found to remotely monitor and act upon information to improve care which would not otherwise have been detected with the opportunities provided by remote real-time access via the EHR (Martin, Tulla, Meltzer, Arora, & Farnan, 2017). A remotely monitored supervisory function could similarly be performed with nursing administrators in that nurse managers could review the data from “brains” of junior nursing personnel to identify training.…”
Section: Discussionmentioning
confidence: 99%
“…More National Health Service (NHS) trusts enable RA-EHR to clinicians including access to live patient observations, electronic prescriptions, radiology and pathology databases, clinic letters and emails. Studies have shown senior clinicians accessing clinical information remotely had contacted junior teams to make changes in clinical management, postulating that it may serve to improve patient safety 1 2. However, there is potential for clinicians to invest more of their personal time to clinical commitments, leading to burnout and stress 3 4.…”
mentioning
confidence: 99%